Lactiplantibacillus argentoratensis and Candida tropicalis Isolated from the Gastrointestinal Tract of Fish Exhibited Inhibitory Effects against Pathogenic Bacteria of Nile Tilapia - Noppadon Siangpro; Songkran Chuakrut; Wanna Sirimanapong; Somboon Tanasupawat; Wongsakorn Phongsopitanun; Bunyarit Meksiriporn; Jarungwit Boonnorat; Siripun Sarin; Siriwat Kucharoenphaibul; Rumpa Jutakanoke (Veterinary Sciences, 2023)
with antipathogenic bacteria of Nile tilapia properties. Collectively, AT8/5 and YON3/2 could be potentially used as promising alternatives to existing antibiotic methods to prevent pathogenic bacteria infection in Nile tilapia farming.
Keywords: Aquaculture disease management and microbiota; Probiotics and Fermented Foods; Identification and Quantification in Food